Antimicrobial Susceptibility Pattern of Salmonella enterica Serovar typhi and Para typhi Isolates from Suspected Enteric Fever Patients in Chattogram - Ahmed, Md Shakeel; Mawa, Imranul; Khan, Ayesha Ahmed (IAHS Medical Journal, 2025)
Background: Enteric fever, a systemic infection caused by Salmonella enterica serovar typhi and Para typhi is one of the most common infections in developing countries. Regardless of high endemicity of enteric fever in Bangladesh, there is paucity of studies on prevalence and drug-resistance of the pathogen. This study was done to evaluate the status in antimicrobial susceptibility patterns of Salmonella enterica serovar typhi and Salmonella enterica Para typhi obtained from blood culture in suspected patients of Chattogram. Materials and methods: A cross-sectional descriptive type of study was done at the Ibne Sina diagnostic center for a period of two-year from February 2021 to January 2023. A total of 1230 clinically suspected septicemic patients were enrolled.The samples were collected and processed following standard microbiological techniques and an antibiotic susceptibility test was done on pure culture isolates using disc-diffusion method for the commonly used antibiotics. The data were analyzed by using SPSS version 27 and the results were summarized by using tables and graphs. Results: Among 1230 suspected cases, blood culture positive were 139 (11.3%). Among them male was more prevalent 65.22% to develop enteric fever and female 34.78% .Out of 139 isolated organisms Salmonella enterica serovar typhi was the most common 46.04%, followed by CoNS 16.55%, E. coli 12.95%, Klebsiella spp. 10.07%, Pseudomonas spp. 6.47%, Staphylococcus aureus 4.32% and Salmonella enterica Para typhi 3.60%. Young Adult and Children are more prone to develop enteric fever by Salmonella enterica typhi 43.48% and 42.03%. Among the 64 Salmonella enterica typhi isolates, least resistance was shown to Amikacin 04 (6.25%) Ceftazidime 06 (9.37%) and Amoxiclav 12 (18.75%).High resistance to Azithromycin 56 (87.5%). Salmonella enterica para typhi isolates were excellently sensitive to most of the antibiotics and showed 100% sensitivity to Amikacin, Gentamycin, imipenem and Tazobactam-Piperacillin, followed by 80% sensitive to Amoxiclav, Ceftriaxone, Chloramphenicol, Ciprofloxacin and Levofloxacin. Conclusions: Current study demonstrated a scenario of enteric fever occurrence and trend of antibiotic use in this disease in Bangladesh. Antibiotics should be used judiciously and according to culture and sensitivity report; over the-counter sales of antibiotics must be stopped to prevent risk of developing newer strains of resistant organisms called superbug. IAHS Medical Journal Vol 7(2), December 2024; 87-92